Derepression of β-Lactamase (Penicillinase) in Bacillus cereus by Peptidoglycans - Ozer, Joy Hochstadt (1970)
In Bacillus cereus 569 a cellular inducer of β-lactamase was isolated which has the same constituents and basic structure as the soluble peptidoglycan found in sporulation, extracts from spores, and germination extracts, and which was previously called “spore-peptide.” The material has been extensively purified and characterized. Two acid-soluble, high-molecular-weight peptidoglycan fractions containing muramic acid, glucosamine, diaminopimelic acid, d-aspartate, and d- and l-alanine, -lysine, -glycine, and -glutamate, distinguishable on the basis of size and different amino acid to amino sugar ratios, have been found to be responsible for the observed induction. Both fractions are capable of inducing high levels of β-lactamase in concentrations lower than those of benzyl penicillin required for optimal induction. Several experiments also suggest that it is the accumulation of such soluble peptidoglycan in penicillin-treated cells which leads to induction of β-lactamase and not the penicillin itself. The “spore-peptide” inducer becomes available during sporulation, and endogenous derepression of β-lactamase activity occurs simultaneously. Such derepression also occurs in a strain of B. cereus very sensitive to penicillin and in which both uninduced as well as “spore-peptide”-induced β-lactamase is a small fraction of that produced by the typical penicillinase producer. These results suggest that β-lactamase in B. cereus functions in cell wall metabolism during sporulation.